Faces da duplicidade e reconfigurações míticas em Anjo Negro e Sortilégio - Mistério Negro - Fank, Mayara Zanatta (2020)
This work aims at addressing the plays Dark Angel, of Nelson Rodrigues, and Sortilege – Black Mystery, from Abdias do Nascimento, whose objective consists on the Myths identification and reconfiguration, among them, there are Medeia and Electra, both Greeks tragedies; the Myth of maternal love, emphasizes the social relationship employed on mother and children relationship; as well as that which involves African context, as the Myth of Exum and others Orixas treated by Nascimento, observing how its presences are fitted on the play by the rites and specifics songs which complement each other giving the meaning to the dramatic play’s atmosphere, emphasizing the symbology behind them. Because the question is around the racial prejudice and black people exaltation, the intention is approach the Black Experimental Theatre, in order to understand the manner and the importance which Rodrigues and Nascimento intended with the black actor valorization, for this purpose, some biographical aspects are relevant. By this way, another objective is to analyses the black character’s prejudice, focusing on the result of this question: the duplicity of themselves. The methodologies allow for the interpretation of the myths reconfigurations. This study is based on Gilbert Durand (1996-2012), Otto Rank (1939), Rosset (1988), Bravo (1997) Oliveira (1999), Prado (1988), Faria (2011), Proença Filho (1995), Elisabeth Badinter (1985), Hendrika Halberstadt-Freud (2006), among others.